Development of animation media in citizenship education learning based on HOTS - Elma Tiana; Zaka Hadikusuma Ramadan (Inovasi Kurikulum, 2025)
Rapid technological advances, demand innovation in teaching methods and learning media to improve student engagement and learning outcomes. This research aims to develop learning media in the form of animated videos to improve the learning experience and the effectiveness of learning in the classroom. The main reason for this research is the need for interactive and visually appealing teaching materials, which are in accordance with the characteristics of students and technological developments. This research uses ADDIE (Analysis, Design, Development, Implementation, and Evaluation) method. Products in the form of animated video learning media are validated by media experts, material experts, and linguists. The validation results showed an average score that was categorized as good. Media experts give "excellent" ratings, subject matter experts also give "very practical" ratings, and linguists give "very appropriate" ratings. In conclusion, the animated videos developed are valid, feasible, and effective to improve students' learning motivation, comprehension, and learning outcomes.   Abstrak Kemajuan teknologi yang pesat menuntut adanya inovasi dalam penggunaan metode dan media pembelajaran. Hal ini dapat berpengaruh pada minat belajar, oleh karena itu guru memiliki peran penting dalam pengembangan media pembelajaran bagi peserta didik. Penelitian ini bertujuan untuk mengembangkan media pembelajaran berupa video animasi guna meningkatkan pengalaman belajar dan efektivitas pembelajaran yang dilaksanakan di kelas. Alasan utama penelitian ini adalah kebutuhan akan bahan ajar yang interaktif dan menarik secara visual, sesuai dengan karakteristik siswa dan perkembangan teknologi. Penelitian ini menggunakan kerangka kerja model ADDIE (Analysis, Design, Develop, Implement, Evaluate). Produk berupa media pembelajaran video animasi divalidasi oleh ahli media, ahli materi, dan ahli bahasa. Hasil validasi menunjukkan bahwa skor rata-rata media memiliki kategori ‘baik’. Penilaian media mendapat hasil ‘sangat baik’, penilaian dari segi materi juga mendapat penilaian ‘praktis’, dan secara bahasa media mendapat penilaian ‘sangat sesuai’. Dapat disimpulkan video animasi yang dikembangkan memiliki hasil akhir valid, layak, dan efektif untuk meningkatkan motivasi belajar, pemahaman, dan hasil belajar siswa. Kata kunci: media pembelajaran; pengembangan media; video animasi HOTS